Surface Modification Of 45S5 Bioactive Glass Microspheres For Drug Delivery - Kamarujaman, Nur Maisara (Universiti Sains Malaysia, 2022)
Bioactive glass microspheres (BGM) has captured numerous research interest in biomedical applications because of its biocompatibility and biodegradable properties. In this research work, bioactive glass (BG) 45S5 with composition of 45.0% SiO₂, 24.5% CaO, 24.5% Na₂O, and 6.0% P₂O₅ in weight percentages (wt.%) are use to fabricate BGM via modified melt-quench-emulsion with the concept of Pickering emulsion method. In fabrication of BGM, surface modification on the BG were done using 3-aminopropyltriethoxysilane (APTES) to increase the hydrophobicity of the silica particles. Pickering emulsion with volume ratio of oil to water at 6:4 was formed with dichloromethane (DCM) and treated BG powder as oil phase, and polyvinyl alcohol (PVA) and deionized (DI) water as the aqueous phase. The parameter used in this study are stirring speed (500 rpm, 600 rpm and 700 rpm) and stirring time (1 hour, 2 hour and 3 hour). Characterization involved are Fourier Transform Infrared (FTIR) spectroscopy, Particle Size Analysis (PSA) and Scanning Electron Microscope (SEM), immersion in Hank’s Balance Salt Solution (HBSS) and pH measurement. From the result obtained, BGM fabricated by 600 rpm and 3 hours show better sphericity and was in the range of particle size desired (less than 80 μm). From the bioactivity evaluation, all sample show precipitate form after being immersed in HBSS and increase in pH after 3 days immersion due to increase in concentration of calcium ion in Hank’s Balanced Salt Solution (HBSS).